2013
DOI: 10.3892/ijmm.2013.1236
|View full text |Cite
|
Sign up to set email alerts
|

Decreased cardiac mitochondrial tetrahydrobiopterin in a rat model of pressure overload

Abstract: Abstract. Sustained cardiac pressure overload induces mitochondrial dysfunction and apoptosis of cardiomyocytes leading to pathological cardiac hypertrophy and dysfunction. Mitochondrial nitric oxide synthase (NOS) appears to cause uncoupling, which produces reactive oxygen species (ROS) instead of nitric oxide (NO), by a decrease in the cofactor tetrahydrobiopterin (BH4). This study focused on examining the changes in mitochondrial BH4 levels during cardiac pressure overload. Chronic cardiac pressure overload… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…BH 4 is a redox-active molecule and oxidation to BH 2 plays a significant part in the decreased bioavailability observed in disease states. In accordance with previous reports [22], [23], [24], we have detected biopterins in mitochondria. We also evidence lower levels of BH 4 in the mitochondria of BH 4 -depleted cells and show that, of the remaining, a greater proportion is oxidised.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…BH 4 is a redox-active molecule and oxidation to BH 2 plays a significant part in the decreased bioavailability observed in disease states. In accordance with previous reports [22], [23], [24], we have detected biopterins in mitochondria. We also evidence lower levels of BH 4 in the mitochondria of BH 4 -depleted cells and show that, of the remaining, a greater proportion is oxidised.…”
Section: Discussionsupporting
confidence: 93%
“…Whilst both mitochondrial biopterins and GTPCH localisation have previously been reported [22], [23], [24], the concept of GTPCH producing BH 4 specifically within the mitochondrial compartment is one that merits more thorough investigation. Similarly, BH 4 transport is poorly understood, although it has been suggested that cellular uptake of BH 4 possibly occurs via either urate transporters (URAT1), organic anion transporters (OATs), or multidrug-resistance-associated proteins (MRPs) in the kidney [25].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, BH4 has been reported to be compartmentalized in the cytoplasm and mitochondria. Interestingly, the concentration of BH4 was more than three times higher in mitochondria than in cardiac tissue (Shimizu et al, 2013), suggesting different roles for BH4 in each compartment. In 1972, Rembold and Buff discovered the direct effect of BH4 on the mitochondrial electron transfer chain using isolated mitochondria and sub-mitochondrial particles (Rembold & Buff, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Plenty of experiments showed that NOS is a key determinant of left ventricular function . Whether NOS plays a similar function in the right ventricle remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac function is influenced by eNOS activity . Pressure overload reduces cardiac BH 4 in conjunction with eNOS uncoupling leading to dilatory remodeling, left ventricular hypertrophy, and fibrosis . BH 4 treatment ameliorated preexisting left ventricular hypertrophy and fibrosis .…”
Section: Introductionmentioning
confidence: 99%